Planning, Monitoring and Control of Mechanics Projects by the BIM - CANDELARIO GARRIDO, Alonso; GARCÍA-SANZ-CALCEDO, Justo; SALGADO, David R.; GONZÁLEZ, Alfonso G. (Engineering Transactions, 2017)
This paper presents an analysis of the transfer of information in planning, monitoring and control phases of a structural project using building information modeling (BIM), in order to determine the essential information that should be available in each stage of the project. The results show that the integration of the BIM into the planning of project implementation results in greater control of the model, preventing the occurrence of inefficiencies during development. In addition, the BIM helps to save time and cost because the building is programmed and it is constructed virtually before being built in place. Due to this simulation process, called 4D simulation, it is possible to reduce problems in the project by 20%, and set the deadlines for a more accurate implementing, around 30%, since all project professionals (engineers, contractors, subcontractors, suppliers, etc.) can visualize how the construction advances and help to refine the 4D simulation.